Sustainability of top-performance athletes` mental health and career retirement support services: European major sports organizations` perspective - Guidotti, F.; Di Rocco, F.; Romagnoli, C.; Ciaccioni, S.; Demarie, S.; Capranica, L.; Padua, E. (Frontiers in Sports and Active Living, 2026)
Introduction: